Preservasi Vitamin C, Kapasitas Antioksidan, dan Sensoris Nanas (Ananas comosus) Segar Potong Proses Minimal menggunakan Blansir Suhu Rendah - Rochmah, Alfi Nur; Lazuardi, Earlian Zaka Bintang; Mulyani, Rizka; Adi, Prakoso; Aryani, Yeni; Ngadiarti, Iskari; Alyensi, Fatiyani; Ropitasari, Ropitasari; Abdi, Yenny Febriana Ramadhan; Nadhilah, Dini; Suleman, Dininurilmi Putri; Rizki, Prajwalita Rukmakharisma; Zulfa, Fitriyah (Pro Food, 2025)
Pineapple (Ananas comosus) is a nutrient-rich tropical fruit known for its high content of vitamin C, bromelain enzyme, and phenolic compounds with antioxidant properties, which are prone to degradation during storage. This study investigated the effect of mild heat blanching (40 °C, 50 °C, and 60 °C) on the physicochemical and sensory qualities of blanching-treated fresh-cut pineapple. The blanching process was applied to improve shelf life while preserving key nutritional attributes, particularly vitamin C content, which is sensitive to thermal degradation. Pineapples were pretreated with 0.15% calcium chloride and subjected to blanching for 5 minutes, vacuum-packed, frozen, thawed, and evaluated for antioxidant activity (DPPH method), vitamin C content (iodometry), total soluble solids (TSS), pH, and sensory attributes (hedonic rating). Researchs result showed that blanching at 60 °C significantly preserved vitamin C (865.33 mg/100g) and antioxidant activity (17.39%) compared to using lower temperatures (40 °C, 50 °C), while maintaining acceptable sensory properties. Although blanching reduced TSS and pH compared to fresh pineapple, the treatment at 60 °C achieved the highest preference scores for color, aroma, taste, and texture. The De Garmo effectiveness index identified 60 °C as the optimal blanching temperature, balancing nutritional preservation and consumer acceptability. These findings suggest that controlled blanching at 60 °C is a viable preservation method for fresh-cut pineapple, extending shelf life while maintaining sensory and functional quality.